ANALISA DAYA DUKUNG PONDASI TIANG PANCANG KELOMPOK PADA PEMBANGUNAN JALAN TOL KAPAL BETUNG STA 36+619 - Jonizar, Jonizar; Arfan, Muhammad; Ariyansyah, Refy (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2021)
The Vesic method (1977) is one of the methods used to calculate the bearing capacity of the pile foundation. However, if it is calculated manually, it will be more difficult and feels more time consuming, while to calculate the bearing capacity of the foundation practically, quickly and correctly, it is very necessary to speed up a work. The group foundation that can be an option or substitute for the group foundation in the Betung Toll Road Construction project is a variation that has a carrying capacity value greater than the existing carrying capacity (Diameter 60cm). The method used in this research is manual calculation using the Vesic method (1977) and the Vesic method with the Allpile Software. The results of this study the carrying capacity of group piles at point P1 by means of manual vesic method obtained 27196.747 kN and 27971.51 kN of allpile software, and after being varied with different pile sizes using allpile software the most efficient value was obtained when used for replacing the group foundation in the control room point P2 is a variation of Diameter 50cm with a depth of 24 meters, as many as 30 piles with a volume of 144,243 m3 with a difference of 30% with the volume of exsiting piles.Keywords: Construction of the Kapal Betung Toll Road, Efficiency of Foundation Carrying Capacity